On the presence of sustainable growth trends in the research sector in the RF territories - D. Yu. Fraimovich; M. S. Kolosova; Z. V. Mishchenko (Вестник Северо-Кавказского федерального университета)
Introduction. The work analyzes regional statistics on labor productivity and cost efficiency in the Russian research sector. It also examines international experience in disseminating the knowledge economy.Goal. The paper identifies the stability of the results of the functioning of the research sector in the territories of the federal districts of the Russian Federation.Materials and methods The paper is based on the study of the theoretical foundations for ensuring the effective work of the scientific sector, the review of advanced technological programs in Russia and the world, the justification of a system of quantitative criteria for an objective assessment of the functioning of fundamental science.Results and discussion. The analysis of the dynamics of the level of cost efficiency and labor productivity in the scientific sector by the example of federal districts of the Russian Federation allows the authors to state the presence of ambiguous trends in changes in indicators, as well as the fact of weak synergy between science and business. The scientific significance of the work consists in the use of a system of quantitative criteria to determine the effectiveness of trends in the development of the scientific sphere. The practical significance of the approach is associated with the possibility of monitoring based on the developed performance indicators of researchers in order to maintain general innovative activity in the country and accelerate the dynamics of the introduction of advanced technologies.Conclusion. The value of the study is to justify the need for constant monitoring of the level of impact of scientific processes by regional authorities. The necessary effectiveness should be supported by the state by stimulating cooperation between science and business, accelerated implementation of developments in the real sector of the economy.